Credit Decision Using Pay Later: The Role of Consumptive Behavior and Financial Literacy with Peer Pressure and Self-Control as Moderators - Hansen Hein Rumtutuly; Apriani Dorkas Rambu Atahau (Postgraduate Program Merdeka University, 2023)
Pay Later is an innovation in great demand because of its ease of use by Generation Z compared to a credit card. Generation Z has changed its lifestyle, from loan avoider to loyal user of loan. This study aims to determine whether consumptive behaviour and financial literacy affect credit decisions using pay later and the role of peer pressure and self-control as moderating variables. This study uses quantitative techniques. Data obtained through distributing questionnaires to Generation Z students (students born in 1995-2010 and active users of pay later). By using 94 students selected as respondents by employing a purposive sampling technique, the findings show that consumptive behavior negatively affects the use of pay later. In contrast, financial literacy positively affects the use of pay later. In addition, peer pressure weakens the impact of independent variables on the use of Pay Later, whereas, on the contrary, self-control strengthens the effect of independent variables on the use of Pay Later.DOI: https://doi.org/10.26905/afr.v6i3.11488